2021
DOI: 10.1111/all.15173
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous origin of IgE in atopic dermatitis and psoriasis revealed by B cell receptor repertoire analysis

Abstract: Background: Epicutaneous sensitization is an important route for the production of IgE, and skin inflammation-induced IgE has recently been reported having features of natural antibody. Atopic dermatitis (AD) and psoriasis have differentially increased level of serum IgE; however, the production mechanism of IgE in these inflammatory skin diseases remains unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 29 publications
2
20
0
Order By: Relevance
“…MCs can directly bind to immature dendritic cells (DCs), induce increased expression levels of the costimulators CD86, CD80, and CD40 on the DC surface, indicating DC maturation, and promote the release of T cell-modulating cytokines, such as IFN-γ, IL-12, IL-6, and TGF-β, enhancing the ability of DCs to induce the proliferation of CD4+ T cells and Th1 and Th17 polarization ( 14 ). Increased IL-17A induces IgG memory B cells to produce IgE by class-switch recombination, forming immune complexes containing soluble IgE with psoriasis-associated autoantigens; these are presented to plasmacytoid (p) DCs via FcϵRI, activating pDCs to trigger inflammatory cytokine responses, including IFN-α, IL-6, IL-8, and TNF, involved in the development and maintenance of inflammatory processes in psoriatic lesions ( 15 17 ). Future studies are needed to determine how IgE-FcϵRI interactions precisely affect the activation of multiple immune cells in psoriatic skin lesions.…”
Section: Mast Cells In Psoriasismentioning
confidence: 99%
“…MCs can directly bind to immature dendritic cells (DCs), induce increased expression levels of the costimulators CD86, CD80, and CD40 on the DC surface, indicating DC maturation, and promote the release of T cell-modulating cytokines, such as IFN-γ, IL-12, IL-6, and TGF-β, enhancing the ability of DCs to induce the proliferation of CD4+ T cells and Th1 and Th17 polarization ( 14 ). Increased IL-17A induces IgG memory B cells to produce IgE by class-switch recombination, forming immune complexes containing soluble IgE with psoriasis-associated autoantigens; these are presented to plasmacytoid (p) DCs via FcϵRI, activating pDCs to trigger inflammatory cytokine responses, including IFN-α, IL-6, IL-8, and TNF, involved in the development and maintenance of inflammatory processes in psoriatic lesions ( 15 17 ). Future studies are needed to determine how IgE-FcϵRI interactions precisely affect the activation of multiple immune cells in psoriatic skin lesions.…”
Section: Mast Cells In Psoriasismentioning
confidence: 99%
“…In mouse models, there are two types of IgE induced via natural and adaptive ways ( 178 ). Adaptive IgE is usually produced by B cells and plasma cells, with characteristics such as variable region gene polysomatic high mutation.…”
Section: Ige Is a Link Or Epiphenomena For Atopic Dermatitis And Psor...mentioning
confidence: 99%
“…Therefore, B cells that naturally produce IgE have less polysomatic high mutation and can respond to their own antigens ( 179 ). Some studies have found that high IgE VH mutation and the increased CDR3 diversity along with high serum IgE content in AD and psoriasis patients ( 178 ). In addition, it was found that the serum IgE level of Sequestosome 1/ P62 DKO mice returned to be normal, which was increased in psoriatic lesions, suggesting that this gene has a similar IgE regulation mechanism in psoriasis and AD ( 180 ).…”
Section: Ige Is a Link Or Epiphenomena For Atopic Dermatitis And Psor...mentioning
confidence: 99%
“…It is believed that psoriasis is a disease that is not associated with atopic dermatitis, as evidenced by their extremely rare coexistence [ 6 , 7 ]. However, it does not exclude the coexistence of, for example, an allergy to environmental, food, or contact allergens, which is a factor in individual works [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%